Forgiveness for Adolescents in Orphanages - Rohmah, Nur Laili; Khotimah, Siti Khorriyatul; Utami, Lufiana Harnany (International Conference on Sustainable Health Promotion, 2025)
This research aims to explore the process of forgiveness among adolescents live in orphanages. This research uses a qualitative case study design method to understand the experience of forgiveness among adolescents living in orphanages through their perspective in depth. The data collection method used was in-depth interviews to explore participants’ experiences regarding the forgiveness they experienced in facing various challenges in life in an orphanage environment. The result illustrates the complexity of the forgiveness process which involves not only pain management, but also emotional transformation that allows individuals to release anger and trauma, moving towards inner peace and psychological healing.